2020
DOI: 10.1016/j.ejvs.2019.09.510
|View full text |Cite
|
Sign up to set email alerts
|

Mid- to Long-Term Outcomes in Management of Spontaneous Isolated Coeliac Artery Dissection (SICAD)

Abstract: WHAT THIS PAPER ADDS Currently, there are no studies showing long-term outcomes in the management of isolated mesenteric artery dissection of the coeliac artery (SICAD). This study selectively performed endovascular intervention for symptomatic SICAD patients and found that there was good long term patency with quick symptom resolution. This study draws attention to the need for proper timing for intervention in SICAD, suggesting that the nature of the disease is not always benign, and endovascular stenting ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Original reports or reports from multi-center collaborations were included. Ninety-seven studies ( 1 …”
Section: Methodsmentioning
confidence: 99%
“…Original reports or reports from multi-center collaborations were included. Ninety-seven studies ( 1 …”
Section: Methodsmentioning
confidence: 99%
“…We thank Drs Kakkos, Zampakis, and Verhoeven for their interest in our multicentre study on open juxtarenal abdominal aortic aneurysm repair. 1 Concerning the level of aortic clamping, we reported in this article only juxtarenal abdominal aortic aneurysm (JRAAA) repair defined by no or short proximal aortic neck (<1 cm) without any need for renal revascularisation. This explains why supracoeliac clamping was rarely needed, except in cases of anatomical variations such as renal and superior mesenteric arteries arising from the aorta at the same level or at a short distance.…”
Section: Re Durability Of Open Repair Of Juxtarenal Abdominal Aortic Aneurysmsmentioning
confidence: 99%
“…After an additional survey, it appears that 5 patients (1.6%) fell into this category, mainly due to age 90 years or to a very limited life expectancy owing to another pathology (e.g., cancer, advanced Alzheimer's disease). We read with great interest the recent article by Kang et al 1 The authors concluded that early intervention in symptomatic spontaneous isolated coeliac artery dissection (SICAD) patients may be necessary in over 50% of patients. However, we would like to elaborate on the endovascular management for SICAD.…”
Section: Re Durability Of Open Repair Of Juxtarenal Abdominal Aortic Aneurysmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Splenic artery dissection (SAD) usually originates from dissection of the celiac trunk or the abdominal aorta [ 1 ]. Isolated SAD is extremely rare but life-threatening [ 2 ].…”
Section: Introductionmentioning
confidence: 99%